A Study of The Relationship between Teachers’ Perception towards Professional Development and Their Job Satisfaction at Kunming Hengshui experimental Middle School Chenggong Campus, China - Wu, Dan; Watana Vinitwatanakhun (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
This research sought to determine the relationship between teachers’ perception towards professional development and their job satisfaction at Kunming Hengshui Experimental Middle School Chenggong Campus, China in the 2020-2021 academic year. The researcher collected the data from 100-full-time teachers by using a questionnaire survey from the Kunming Hengshui Experimental Middle School Chenggong Campus, China. To do so, the study evaluated the teachers’ perception towards professional development as well as job satisfaction in which Means and Standard Deviations were used for descriptive and quantitative analysis. Finally, the relationship between these two variables was analyzed and assessed through Pearson Product Moment Correlation Coefficient analysis. The basis for the professional development concept of this study was founded on Guskey’ s (2003) theory of Professional Development. Moreover Herzberg’ s (1959) Motivation-Hygiene theory was the foundation to support the researcher’ s concept of job satisfaction. The research finding indicates that the teachers at the Kunming Hengshui Experimental Middle School Chenggong Campus, China had a relatively high perception towards the professional development and job satisfaction. A high positive relationship between teachers’ perception towards professional development and their job satisfaction was identified in the Kunming Hengshui Experimental Middle School Chenggong Campus, China.